MINIMIZING SOCIAL RISKS IN THE WORK OF JUDGES, WHO ARE PERSONS WITH DISABILITIES - BARSUK, MARYNA (Ehrlich's Journal, 2024)
Abstract. The article analyzes the problems of social protection for judges who are persons with disabilities within the context of their professional activities in Ukraine. The author examines the integration of people with disabilities into the justice system, emphasizing the importance of ensuring equal working conditions for all judges, regardless of their physical condition. The article pays special attention to the main social risks faced by judges with disabilities, such as psychophysiological stress, high levels of stress, and potential health complications that may arise from their conditions in intense work environments. The author notes that the existing forms of social protection are not always sufficient to mitigate the specific risks associated with disability. This insufficiency can lead to negative consequences for both the health and efficiency of judges. The article analyzes Ukrainian and foreign legislation, focusing primarily on Polish laws, regarding the regulation of working time and intensity for judges with disabilities. Based on an analysis of the legislation and practical outcomes, the author formulates recommendations for improving Ukrainian legislation. It is proposed to introduce a special working regime for persons with disabilities, which would include reduced working hours, a ban on overtime work, and prohibition of night work. It is also recommended to adapt the legislation concerning the judicial system and the status of judges to accommodate this new working regime, to avoid the social and legal dilemmas associated with the performance of judicial duties by persons with disabilities. Specifically, it is proposed to amend the Law of Ukraine «On the Judicial System and Status of Judges» by adding Article 135-1, titled “Judge’s Working Time.” This new article would first stipulate that a judge's working time is determined by the scope of their tasks. Secondly, it would establish a rule that judges who are persons with disabilities should not be required to perform tasks at night or work overtime, except in cases explicitly provided for by law. Thirdly, Article 135-1 should establish a rule stating that judges who are persons with disabilities (belonging to disability groups II or I) cannot work more than 7 hours a day and 35 hours a week. The proposals formulated in the article aim to improve legislation and will help create conditions for equal access of persons with disabilities to professional activities in the justice system. This is an important step towards fostering an inclusive society.